정신보건사회복지사 포커스집단면접을 통한 정신보건서비스 전달체계에 대한 인식 조사 - 박수빈, 전진용, 남윤영, 임희영, 이다영, 김은진, 홍진표, 최성구, 하규섭 (Singyŏng chŏngsin ŭihak, 2016)
ObjectivesZZTo use focus-group interviews (FGI) to determine the current state of the Korean mental health service delivery system, inter-agency patient links, and identify associated problems. MethodsZZThe FGI were conducted by seven workers from psychiatric rehabilitation centers and community mental health centers and seven social workers from mental health hospitals. ResultsZZWithin the mental health service delivery system, disconnection of the community network after discharge is considered a serious problem. The following improvement proposals are suggested : 1) the control tower should govern the community network after discharge, 2) consider insurance costs during activation of hospital links, and 3) expand information sharing related to community social facilities. With regard to non-voluntary admission and long-term hospitalization, most focus group members considered the revolving-door phenomenon to be more serious than non-voluntary admission. In order to prevent unnecessary long-term hospitalization, the FGI results indicated that the government should proactively intervene in the admission/discharge process. In addition, the following improvement proposals were suggested : 1) functional activation of the mental health review board via the reinforcement of workers’ expertise, 2) expansion of local mental health centers, and 3) undertake institutional changes related to the family-related issue of preferring hospitalization over a stay at a secure facility. ConclusionZZFor the government to improve the efficiency of the mental health service delivery system, it is necessary to improve institutional linkages, expand mental health infrastructure, and develop an integrated management system. KCI Citation Count: 0